Macromolecular organic compounds from the depths of Enceladus - Postberg, Frank; Khawaja, Nozair A.; Klenner, Fabian; Nölle, Lenz; Reviol, René; Trieloff, Mario (Nature, 2018)
The detection of complex organic molecules with masses higher than 200 atomic mass units in ice grains emitted from Enceladus indicates the presence of a thin organic-rich layer on top of the moon’s subsurface ocean.
Published online 27 June 2018
Gesehen am 17.07.2018